An Adipose-Derived Injectable Sustained-Release Collagen Scaffold of Adipokines Prepared Through a Fast Mechanical Processing Technique for Preventing Skin Photoaging in Mice - Jin, Xiaoxuan; Zhang, Yuchen; Zhang, Xiangdong; Li, Yibao; Xu, Mimi; Liu, Kaiyang; Ru, Jiangjiang; Ma, Chijuan; Yao, Yao; He, Yunfan; Gao, Jianhua (Frontiers in Cell and Developmental Biology, 2021)
Ultraviolet A (UVA) radiation is the major contributor to skin photoaging, associated with increased collagen degradation and reactive oxygen species (ROS) expression. Adipokines have been proven as promising therapeutic agents for skin photoaging. However, adipokine therapy is generally limited by the short in vivo release duration and biological instability. Therefore, developing a treatment that provides a sustained release of adipokines and enhanced therapeutic effects is desirable. In this study, we developed a novel mechanical processing technique to extract adipose tissue-derived ECM components, named the “adipose collagen fragment” (ACF). The physical characterization, injectability, collagen components, residual DNA/RNA and adipokine release pattern of ACF were identified in vitro. L929 cells were treated with ACF or phosphate-buffered saline for 24 h after UVA irradiation in vitro. The expression of senescence-associated β-galactosidase (SA-β-gal), ROS and antioxidase were investigated. Then, we evaluated its therapeutic efficacy by injecting ACF and phosphate-buffered saline, as a control, into the dermis of photoaging nude mice and harvesting skin samples at weeks 1, 2, and 4 after treatment for assessment. The content of adipokines released from ACF was identified in vivo. The collagen synthesis and collagen degradation in ACF implants were evaluated by immune staining. Dermal thickness, fibroblast expression, collagen synthesis, ROS level, antioxidase expression, capillary density, and apoptotic cell number were evaluated by histological assessment, immune staining, and polymerase chain reaction in the skin samples. We demonstrated that ACF is the concentrated adipose extracellular matrix collagen fragment without viable cells and can be injected through fine needles. The lower expression of SA-β-gal, ROS and higher expression of antioxidase were observed in the ACF-treated group. ACF undergoes collagen degradation and promotes neocollagen synthesis in ACF implants. Meanwhile, ACF serves as a sustained-release system of adipokines and exhibits a significantly higher therapeutic effect on mouse skin photoaging by enhancing angiogenesis, antioxidant abilities, antiapoptotic activities, and collagen synthesis through sustainedly releasing adipokines. To sum up, ACF is an adipokines-enriched, sustained-release extracellular matrix collagen scaffold that can prevent UVA-induced skin photoaging in mice. ACF may serve as a novel autologous skin filler for skin rejuvenation applications in the clinic.